2022
DOI: 10.3390/en15031099
|View full text |Cite
|
Sign up to set email alerts
|

Management of Radioactive Waste from HTGR Reactors including Spent TRISO Fuel—State of the Art

Abstract: In light of the increasing demand for energy sources in the world and the need to meet climate goals set by countries, there is growing global interest in high temperature gas cooled reactors (HTGRs), especially as they are known to be inherently safe nuclear reactors. The safety of HTGRs results, among other, from the nature of the nuclear fuel used in them in the form of coated TRISO particles (tri-structural-isotropic) and the reduction of the total amount of radioactive waste generated. This paper reviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
6
0
2
Order By: Relevance
“…Applying the Rietveld full-profile method to evaluate the contributions of the two phases in the structure of the investigated samples, it was found that the phase ratio is PyC:SiC = 73.3:26.7. Analysis of the crystal lattice parameters and volume for the SiC phase made it possible to establish that the integral porosity value of the examined samples is 1.61%, at a phase density of 3.134 g/cm 3 . The degree of crystallinity of the ceramic layer of silicon carbide is more than 95%, which indicates a high degree of structural ordering.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Applying the Rietveld full-profile method to evaluate the contributions of the two phases in the structure of the investigated samples, it was found that the phase ratio is PyC:SiC = 73.3:26.7. Analysis of the crystal lattice parameters and volume for the SiC phase made it possible to establish that the integral porosity value of the examined samples is 1.61%, at a phase density of 3.134 g/cm 3 . The degree of crystallinity of the ceramic layer of silicon carbide is more than 95%, which indicates a high degree of structural ordering.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that, in the initial state, the sphere surface has a developed structure consisting of fine-grained inclusions located on the surface with a high proportion of uniformity. Using the method of X-ray phase analysis, it was found that for the SiC phase the value of integral porosity of the studied samples is 1.61%, with a phase density of 3.134 g/cm 3 . The degree of crystallinity of the ceramic layer of silicon carbide is more than 95%, which indicates a high degree of structural ordering.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Для решения всех вышеуказанных требований, как правило, в качестве основы инертных матриц используют тугоплавкие оксидные соединения, а также их смеси, что позволяет совместить положительные качества оксидных соединений и получить материал, обладающий большими перспективами использования в качестве дисперсного ядерного топлива [8][9][10].…”
Section: Introductionunclassified
“…Kiegiel et al [2] present the final part of the HTGR fuel cycle. The review presents many methods that could be employed to ensure the sustainable, feasible management and longterm storage of HTGR nuclear waste in order to protect the environment and society.…”
mentioning
confidence: 99%